Мультикультуралізм як потенційна складова культурної політики України - Маліков, Василь Володимирович (НТУ "ХПІ", 2016)
У цій статті автор осмислює мультикультуралізм як концепцію і політику та розглядає переваги його реалізації для України. Дослідження зосереджується на ідеологічній підґрунті та концептуальному розумінні мультикультуралізму в сучасному українському та світовому наукових дискурсах. Автор робить висновок про те, що мультикультуралізм як потенційна частина культурної політики може бути корисним у багатьох відношеннях. Він матиме позитивний вплив на добробут і стабільний розвиток місцевих спільнот, регіональне зростання і соціально-економічне пожвавлення, піднесення міського життя і розвиток туризму.

This paper reviews multiculturalism as a concept and a policy and argues the advantages of its implementations for Ukraine. The research focuses upon ideological basis and conceptual understanding of multiculturalism in contemporary Ukrainian and international scientific discourses. Multiculturalism may help to secure a principle of respect for cultural diversity and support sustainable development of sociocultural groups in Ukrainian society nowadays. The author concludes that the multiculturalism as a potential integral part of cultural policy may be beneficial in many ways. It will have a positive impact on the wellbeing and sustainability of local communities, regional growth and revival, the development of urban life and the rise of tourism, as well as the promotion of national interests on international level.
Multiculturalism as a potential component of the Ukrainian cultural policy
Keywords: соціально-культурні групи; ліберальний підхід; сталий розвиток; права людини; гуманізм.; multiculturalism; sociocultural groups; cultural policy; sustainable development; human rights; humanism